Sustained beneficial infections: priority effects, competition, and specialization drive patterns of association in intracellular mutualisms - Hill, Malcolm; Lawson, Barry; Cain, John W.; Rahman, Nasheya; Toolsidass, Shiv; Wang, Tongyu; Geraghty, Sara; Raymundo, Eberardo; Hill, April (Frontiers in Ecology and Evolution, 2023)
Intracellular symbioses provide a useful system for exploring evolutionary and ecological forces that shape mutualistic partnerships. Within- and among-host competitiveness driven by different strategies that symbionts adopt as they transfer materials to the host across a sub-cellular membrane might explain patterns of host:symbiont association observed in natural systems. We tested the hypothesis that different translocation strategies employed by symbionts affect their ability to occupy host habitats using two distinct modeling approaches. The first involved constructing a deterministic, Lotka-Volterra-type model with two symbiont species competing for access to a single host. The model recovered expected behaviors of co-occupancy/coinfection as well as competitive exclusion. However, a specialization coefficient allowed advantages to accrue to one of the symbionts and permitted otherwise inferior competitors to displace superior competitors. The second approach involved developing and implementing a detailed, highly configurable, and realistic agent-based model (ABM), facilitating experimentation of multiple symbiont strategies in competition simultaneously. The ABM emphasizes bidirectional movement of materials between symbiont and host (e.g., photosynthate from algae to heterotrophic host). Competitive interactions between symbionts based on simple strategies led to exclusion of the inferior symbiont or co-occupancy of the host. As in the first model, inferior competitors could overtake superior competitors when 'affinity' terms (i.e., specialization) were included in the model. Both models lay bare the importance of coevolutionary specialization as a selectively advantageous strategy, and they offer a new conceptual framework for interpreting the dynamic patterns observed in extant host and mutualist associations by challenging the idea of 'host control' of outcomes, and identifying specific points where coevolutionary specialization might accrue.